2006
DOI: 10.1111/j.1365-2567.2006.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte antigen‐4‐dependent down‐modulation of costimulatory molecules on dendritic cells in CD4+ CD25+ regulatory T‐cell‐mediated suppression

Abstract: We have previously demonstrated that CD4+ CD25+ natural regulatory T cells (Treg cells) induce down-modulation of CD80 and CD86 (B7) molecules on dendritic cells (DCs) in vitro. In this report we show that the extent of down-modulation is functionally significant because Treg-cell conditioned DCs induced poor T-cell proliferation responses. Further, we report that down-modulation was induced rapidly and was inhibited by blocking cytotoxic T lymphocyte antigen-4 (CTLA-4), which is constitutively expressed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
186
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(201 citation statements)
references
References 54 publications
8
186
1
6
Order By: Relevance
“…-1155 Whether a certain CTLA4 expression threshold is necessary to downmodulate CD80/CD86 expression on DCs requires further investigation. CTLA4 has been shown to be involved in Treg cell-mediated inhibition of DC maturation [6,8]. However, it was not known whether CTLA4 alone is sufficient to induce tolerogeneic DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-1155 Whether a certain CTLA4 expression threshold is necessary to downmodulate CD80/CD86 expression on DCs requires further investigation. CTLA4 has been shown to be involved in Treg cell-mediated inhibition of DC maturation [6,8]. However, it was not known whether CTLA4 alone is sufficient to induce tolerogeneic DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro methods have been developed in order to generate tolerogenic DCs [5]. Additionally, a growing body of experimental data highlights the role of Treg cells in maintaining tolerance through the suppression of DC immunostimulatory capacity [6][7][8][9]. However, the molecular mechanisms by which Treg cells modulate DC function remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, our data suggest that CD4 + CD25 + CD134 + CD39 + Treg cells, in the context of a chronic viral infection such as CMV, may rely on the functions of CTLA-4 and CD39, as the expression of both molecules correlates with suppressive function of CMV-P1-specific T-cell clones. Both of these molecules have been shown to effect suppression of responder cells through interaction with DCs [11,54], indicating a potentially important role for DC interaction in the suppressive function of CD4 + CD25 + CD134 + CD39 + Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data suggest that CD4 + CD25 + CD134 + CD39 + Treg cells, in the context of a chronic viral infection such as CMV, may rely on the functions of CTLA-4 and CD39, as the expression of both molecules correlates with suppressive function of CMV-P1-specific T-cell clones. Both of these molecules have been shown to effect suppression of responder cells through interaction with DCs [11,54], indicating a potentially important role for DC interaction in the suppressive function of CD4 + CD25 + CD134 + CD39 + Treg cells.Lastly, we applied our ex vivo methodology in a clinical setting by measuring HIV-Gag-specific responses both before and after commencement of ART in the RESTORE study. We observed that the percentage of CD39 − cells within CD25 + CD134 + HIV-Gag-specific CD4 + T cells at baseline was significantly associated with greater CD4 + T-cell recovery after ART initiation and additionally that this percentage inversely correlated with baseline HIV viral load.…”
mentioning
confidence: 99%
“…Among these, CD4 + CD25 + Foxp3 + T cells express the immunoglobulin cytotoxic T‐lymphocyte antigen 4 (CTLA‐4), the interleukin (IL)‐2 receptor CD25, and produce inhibitory cytokines such as IL‐10 and transforming growth factor (TGF)‐β 2, 3. CD4 + CD25 + Foxp3 + T cells express CD25 at high levels and sequester IL‐2 accordingly, rendering these T cells prone to apoptosis 4.…”
Section: Introductionmentioning
confidence: 99%